Conditions for regularity and for 2-connectivity of Toeplitz graphs - Akbari S.; Ghorban, S. Hossein; Malik S.; Qajar S. (Utilitas Mathematica, 2019)
Let 1 < ti < t2 < ••• < th < n. A Toeplitz graph G = (V,E) denoted by Tn(tiy ..., f) is a graph where V = {1,. .. ,n} and E = {(m) I i-JI. • • >}}•this paper, we classify all regular Toeplitz graphs. Here, we present some conditions under which a Toeplitz graph has no cut-edge and cut-vertex. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.